Second language speaking anxiety among Malaysian postgraduate students at a Faculty of education - Badrasawi, Kamal J I; Solihu, Abdulateef; Tunku Ahmad, Tunku Badariah (Australian International Academic Centre PTY.LTD, 2020)
This study examined the level of L2 speaking anxiety among school teachers undertaking a master’s degree at the International Islamic University Malaysia and sought to determine if the anxiety level would diﬀer by gender, school location and teaching subject. A convenience sample of 290 teachers completed a 12-item survey on L2 speaking anxiety adapted from Nazir et al. (2014). The survey data were analyzed using the Rasch measurement modeling for polytomous data, independent samples t-test and one-way ANOVA. Overall, the respondents did not show high levels of speaking anxiety, (Mean -.89 logits). Most were largely worried about being able to express themselves eﬀectively in English (-.66 logits), making mistakes in speaking (-.31 logits), and how lecturers would react to their mistakes (-.38 logits). The sample’s speaking anxiety scores were found to diﬀer signifcantly by teaching subject, while no statistically signifcant diﬀerences were observed in regard to gender and school location. The results imply that the teachers need to be helped in terms of confronting the factors that cause them to be anxious about speaking in English. In terms of research, in-depth qualitative studies need to be undertaken to further understand the nature of L2 speaking anxiety among schoolteachers, while quantitative studies with larger samples are recommended to uncover underlying factors of speaking anxiety